Engineering of chalcogenide materials for embedded applications of Phase Change Memory. (September 2015) - Zuliani, Paola; Palumbo, Elisabetta; Borghi, Massimo; Dalla Libera, Giovanna; Annunziata, Roberto
Highlights: PCM is proposed as key differentiator for next generation embedded applications. Overcoming limitations of PCM for high temperature data retention is discussed. Chalcogenides can be engineered in the Ge-rich region of Ge–Sb–Te ternary diagram. The trade-off between cell performances and RESET thermal stability is discussed. Selected alloys show reliability performance in line with automotive specifications. Abstract: Phase Change Memory technology can be a real breakthrough for process cost saving and performances for embedded applications. The feasibility at 90 nm technology node has been solidly proven in an industrial environment and the added value of this solution demonstrated. Nevertheless, for specific applications some improvement in High Temperature Data Retention (HTDR) characteristics is needed. In this work we present the engineering of chalcogenide materials in order to increase the stability of RESET state as a function of temperature. This goal has been achieved by exploring Ge-rich compounds in the Ge–Sb–Te ternary diagram. In particular, an optimized Ge x Sb y Te z Phase Change material, able to guarantee code integrity of the memory content after soldering thermal profile and data retention in extended temperature range has been obtained. Extrapolation of data retention at 10 years for temperatures higher than 150 °C cell-level has been demonstrated, thus enabling automotive applications.